2018
DOI: 10.1021/acs.accounts.8b00307
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Brushes: Efficient Synthesis and Applications

Abstract: Polymer brushes are special macromolecular structures with polymer chains densely tethered to another polymer chain (one-dimensional, 1D) or the surface of a planar (two-dimensional, 2D), spherical or cylindrical (three-dimensional, 3D) solid via a stable covalent or noncovalent bond linkage. In comparison with the corresponding linear counterpart with similar molecular composition, one-dimension polymer brushes have some fascinating properties including wormlike conformation, compact molecular dimension, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
192
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(194 citation statements)
references
References 44 publications
1
192
0
1
Order By: Relevance
“…[9][10][11][12][13] Up to now,al arge number of sensors based on AIEgens have been developed. [14][15][16][17][18][19][20] Some of them show valuablea pplication prospecti nm onitoring,a nalysis, imaging of ions. [16][17][18][19][20] However,r esearch work on anion sensors based on AIE effect was relatively little.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13] Up to now,al arge number of sensors based on AIEgens have been developed. [14][15][16][17][18][19][20] Some of them show valuablea pplication prospecti nm onitoring,a nalysis, imaging of ions. [16][17][18][19][20] However,r esearch work on anion sensors based on AIE effect was relatively little.…”
mentioning
confidence: 99%
“…[14][15][16][17][18][19][20] Some of them show valuablea pplication prospecti nm onitoring,a nalysis, imaging of ions. [16][17][18][19][20] However,r esearch work on anion sensors based on AIE effect was relatively little. Gao et al reported that monoimidazolium with AIE effect could selectively recognize H 2 PO 4À in acetonitrile, but could not do in water.…”
mentioning
confidence: 99%
“…In addition, the extent of the interfacial response and the performance of synthetic ion channels bearing functional materials within a particular application domain can be finely modulated by decorating the surface of channels with an appropriate set of functionalities at a precisely controlled surface functional group density [67,68]. In this context, surface-tethered assemblies of carefully designed macromolecules widely known as polymer brushes [69][70][71] have emerged as an effective avenue enabling precise control over the surface chemical functionality and functional group density. The emergence of hybrid materials derived from the combination of polymer brushes and synthetic ion channel platforms has played a key role in diversifying their respective application profile resulting in the development of a variety of functional hybrid materials.…”
Section: Polymer Brush-functionalized Nanoporous Substrate As Proton mentioning
confidence: 99%
“…Polymer brushes could find promising applications in various areas such as responsive surfaces, non-biofouling surfaces, cell adhesive surface, protein binding and immobilization, chromatography supports, membrane applications, antibacterial coatings, and low friction surfaces. [1][2][3][4][5][6][7][8][9][10][11][12] These applications usually require polymer brushes to have a desired thickness. For instance, at least 100 nm is required for polymer brushes to reduce friction coefficient.…”
Section: Ultra-thick Polymer Brushesmentioning
confidence: 99%